Structural relaxation in pure liquids: Analysis of wavenumber dependence within the approach of generalized collective modes - Bryk, T.; Mryglod, I. (Condensed Matter Physics, 2008)
Wavenumber dependence of structural relaxation in liquids is studied by the method of generalized collective modes (GCM). A new perturbation approach within the GCM method is proposed and applied in the longwavelenth limit in order to obtain analytical expressions for the wavenumber-dependent structural relaxation and sound dispersion within a simplified three-variable dynamical model. Analytical results are compared with numerical study of generalized modes within a more general five-variable dynamical model, which accounts for thermal processes in liquids. Numerical results are presented for four thermodynamic points of Lennard- Jones fluid at the reduced temperature T* = 1.71. We discuss the features of non-hydrodynamic process of structural relaxation in different regions of wavenumbers.